Exploring Novel Biologically-Relevant Chemical Space Through Artificial Intelligence: The NCATS ASPIRE Program - Duncan, Katharine K.; Rudnicki, Dobrila D.; Austin, Christopher P.; Tagle, Danilo A. (Frontiers in Robotics and AI, 2020)
In recent years, artificial intelligence and machine learning have become increasingly important to the biomedical research community. These technologies, coupled to big data and cheminformatics, have tremendous potential to improve the design of novel therapeutics and to provide solutions to patients. Leveraging advances in machine learning, automated synthetic chemistry, and high-throughput biology, an NCATS program, A Specialized Platform for Innovating Research Exploration (ASPIRE), seeks to transform drug discovery and eliminate the bottlenecks in translational science. Here we discuss the opportunities and challenges surrounding the application of machine learning to the exploration of biologically-relevant chemical space as part of ASPIRE.